Pengaruh Human Capital Terhadap Kinerja Aparatur Sipil Negara - Nazaldi, Honest; Wardi, Jeni; Supeno, Bambang (Student Journal of Business and Management, 2025)
Good performance management of state civil servants requires reliable human capital, which has knowledge, expertise, abilities, and skills for carrying out its main tasks and functions. However, problems with its implementation still involve complaints from the public regarding the performance of the state civil apparatus, especially in Bantan District, Bengkalis Regency. The aim of this research is to analyze the influence of human capital on the performance of state civil servants. The research method is quantitative and descriptive, with a sample of 37 state civil servants and data processing using linear regression. Research findings show that knowledge partially has a negative effect on the performance of state civil servants, and expertise, abilities, and skills partially have a positive effect on the performance of state civil servants. Simultaneously, knowledge, expertise, abilities, and skills have a positive influence on the performance of the state civil apparatus. The implication of these findings is that the leadership of Bantan District, Bengkalis Regency, needs to improve the performance of state civil servants in public services and teamwork in achieving work effectiveness and efficiency.